2006
DOI: 10.2460/javma.229.5.694
|View full text |Cite
|
Sign up to set email alerts
|

Development of antimicrobial drug resistance in rectal Escherichia coli isolates from dogs hospitalized in an intensive care unit

Abstract: Results suggested that the proportion of rectal E coli isolates obtained from dogs housed for >or= 3 days in a veterinary teaching hospital ICU that were resistant to antimicrobial agents increased as the duration of hospitalization in the ICU increased. Thus, ICU hospitalization time should be as short as possible to prevent development of antimicrobial resistance among rectal E coli isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
(20 reference statements)
6
33
1
Order By: Relevance
“…Results from the simulations done with randomized parameter values and subsequent regression analyses suggest that the model is consistent with previous reports that the incidence of both resistant and non-resistant strain colonization increases with increasing length of stay in the hospital [14], [15], [33]. As long as the number of patients already hospitalized is below the maximum capacity for the hospital, longer patient stays contribute to a higher number of hospitalized patients, leading to more interactions between patients, healthcare workers and transmission points.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Results from the simulations done with randomized parameter values and subsequent regression analyses suggest that the model is consistent with previous reports that the incidence of both resistant and non-resistant strain colonization increases with increasing length of stay in the hospital [14], [15], [33]. As long as the number of patients already hospitalized is below the maximum capacity for the hospital, longer patient stays contribute to a higher number of hospitalized patients, leading to more interactions between patients, healthcare workers and transmission points.…”
Section: Discussionsupporting
confidence: 86%
“…It is well documented that antimicrobial use is associated with antibiotic resistance [6], [14], [33], [44], but our model indicates that giving an early effective antibiotic therapy has no significant impact on either reducing or increasing the incidence of antibiotic resistance. This might be a result of the relatively short average length of stay of the patients and shorter time available for antibiotic therapy completion.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The enrollment of several hospitals and clinics reduces the risk of overrepresentation of the resident house flora, including susceptibility patterns, of any individual care facility. It has previously been stated that, as referral hospitals are more likely to have a higher caseload of complicated cases in need of prolonged antimicrobial treatment, less susceptible isolates should be expected in samples originating from referral hospitals compared to smaller clinics [3,41-44]. Associations between antimicrobial treatment and isolating resistant bacteria from SSIs are beyond the scope of this study, and statistical assessments of trends was not possible due to too few resistant isolates originating from cases treated for longer than one day.…”
Section: Discussionmentioning
confidence: 99%
“…Oral treatment of dogs with cephalexin has been proposed as a selector of CMY-2-producing E. coli in their faecal microbiota (Damborg and others 2011). One study carried out in a veterinary ICU showed that the proportion of dogs carrying resistant E. coli increased with duration of hospitalisation and with the use of antimicrobial drugs (Ogeer-Gyles and others 2006). Our study is in agreement with the previous observations and even though hospitalisation in the last year did not influence the occurrence of ESBL- and pAmpC-producing E. coli , our analyses indicate that the use of antimicrobials in the last year was the major factor associated with ESBL- and pAmpC-producing E. coli .…”
Section: Discussionmentioning
confidence: 99%